Czech Republic : Selected Issues in Fiscal Policy Reform. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Selected Issues paper examines two key questions on fiscal policy reform in the Czech Republic. First, how can the fiscal institutional framework be strengthened to maintain discipline and enhance transparency? Second, what are the priorities in expenditure reform that can be implemented without sacrificing the quality of spending? The paper discusses the recent Czech experience with the medium-term expenditure framework and some proposals for strengthening it. It also discusses cross-country analyses of spending efficiency and flexibility, and proposes areas for fiscal adjustment that reduce inefficiencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet